2017
DOI: 10.1590/s0100-736x2017000900017
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones affect decidualization and angiogenesis in the decidua and metrial gland of rats

Abstract: RESUMO.-[Hormônios tireoidianos afetam a decidualização e a angiogênese na decídua e glândula metrial de ratas.] Este estudo teve como objetivo avaliar os efeitos dos hormônios tireoidianos sobre a decídua e a glândula metrial pela análise da expressão de fatores angiogênicos em ratas. 72 ratas adultas, fêmeas foram distribuídas nos grupos hipotiroideo, tratado com T 4 e controle. Aos 10, 14 e 19 dias de gestação (DG), a decídua e a glândula metrial foram coletadas para avaliação histomorfométrica e imunoistoq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…THs appear to facilitate decidualization, as evidenced by their impairment in hypothyroid rats [ 112 ]. Some of these effects may be mediated through altered expression of growth factors and angiogenic molecules such as VEGF [ 113 , 114 ]. Increased levels of leukemia inhibitory factor may also explain this phenomenon, as it is known to be involved in the process of decidualization and implantation and demonstrate elevated expression in response to TSH [ 23 , 115 ].…”
Section: Thyroid Hormones and Reproductive Physiologymentioning
confidence: 99%
“…THs appear to facilitate decidualization, as evidenced by their impairment in hypothyroid rats [ 112 ]. Some of these effects may be mediated through altered expression of growth factors and angiogenic molecules such as VEGF [ 113 , 114 ]. Increased levels of leukemia inhibitory factor may also explain this phenomenon, as it is known to be involved in the process of decidualization and implantation and demonstrate elevated expression in response to TSH [ 23 , 115 ].…”
Section: Thyroid Hormones and Reproductive Physiologymentioning
confidence: 99%
“…Maternal hypothyroidism is one of the most common gestational metabolic disorders and affects around 2–3% of the population [ 1 ]. Women with maternal hypothyroidism have an increased risk of miscarriage, premature birth, placental abruption, preeclampsia, gestational diabetes, and intrauterine growth restriction [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ], while in hypothyroid female rats the placental development is compromised, with alteration of immunology and trophoblastic endocrine function [ 7 , 9 , 10 , 11 , 12 , 13 , 14 ]. In addition, a recent study demonstrated that maternal hypothyroidism also causes oxidative stress and endoplasmic reticulum stress at the maternal-fetal interface of rats [ 15 ], suggesting that this cellular stress may result from the failure of intrauterine trophoblastic migration observed in these animals [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our team has studied the changes in the maternal-fetal interface caused by thyroid dysfunctions that result in placental insufficiency and consequently in intrauterine growth restriction (IUGR) [6][7][8][9][10]. IUGR predisposes adults to diseases of the locomotor system, such as osteoarthritis [11].…”
Section: Introductionmentioning
confidence: 99%